PP.09.33: ADRENAL VEIN CATHETERISATION GUIDED BY FAST CORTISOL ANALYSIS, AND WITH CONTINUOUS SAMPLING DURING 30 MINUTES FROM THE LEFT ADRENAL VEIN. (June 2015) - Andersen, U.
Abstract : Objective: To report the results of 11 adrenal vein catheterisations made in 2013 after introducing a bedside analysis of cortisol with response after 12 minutes. Furthermore, to report the results of 30 minutes continuous sampling from the left adrenal vein. Design and method: 11 consecutive patients with primary hyperaldosteronism and hypokaliemia, referred for adrenal vein catheterisation. Catheters were placed under fluoroscopic guidance. Contrast injection was used as necessary to confirm correct placement. Fast cortisol analysis with response time12 minutes confirmed that samples were representative of adrenal vein blood. In 10 patients, blood samples were drawn every second minute during 30 minutes. Results: Succesfull sampling from both adrenals was obtained in 9 of 11 patients (82%). 7 patients had unilateral hypersecretion with suppression of the contralateral secretion, while 2 had bilateral secretion. Sampling with analysis af aldosterone an cortisol showed great variations over time of the key parameter aldosterone/cortisol ratio in blood from hypersecreting adrenals (with ratios between highest and lowest values ranging from 3, 3 to 8, 9) but also from suppressed adrenals (with ratios between 1, 6 and 4). The main reason for the variations were aldosterone secretory peaks. Conclusions: The rate of succesful bilateral sampling from adrenal veins has inproved from approximately 60 % to 82% after introducing a method for fast cortisol analysis. There are great variations in aldosterone/ cortisol ratio over time. Multiple sampling with intervals of several minutes are recommended. Figure. No caption available.